TEORI FEMINISME: SEJARAH, PERKEMBANGAN DAN RELEVANSINYA DENGAN KAJIAN KEISLAMAN KONTEMPORER - Nuril Hidayati (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2018)
Abstract. Feminism as a system of ideas is a broad-based framework and study of social life and human experience that evolves from a women-centered perspective. It’s long history is a mirror of the batle on how to bring about justice for humanity to be real. Feminism ignites the Muslim consciousness of the reality of gender inequality. This awareness leads to the understanding that the estrangement of gender imbalances begins with the disparity of the meaning of religious texts with the reality of the historicity. The fusion between feminist theory as part of modern theory and islamic studies (contemporary interpretation of religious law) offers the solution of humanitarian problems through a balanced of judgment in women and men. Finding relevant Islamic values in gender mainstreaming has a positive impact on social justice. Developing Islamic studies as how to find the esoteric value that underlies life within the framework of religious social transformation. Affirming that Islam does not merely address the classical and theological issues of Fiqh, but also inspires human beings to judge and treat their fellow human beings as God's creatures with dignity and prestige so it is natural to be respected and treated fairly. Abstrak. Feminisme sebagai sistem gagasan sebagai kerangka kerja dan studi kehidupan sosial dan pengalaman manusia yang berevolusi dari perspektif yang berpusat pada perempuan. Ini sejarah panjang sebagai cerminan dari tanggung jawab tentang bagaimana mewujudkan keadilan bagi umat manusia menjadi nyata. Feminisme menyulut kesadaran Muslim tentang realitas ketidaksetaraan gender. Kesadaran ini mengarah pada pemahaman bahwa pengasingan ketidakseimbangan gender dimulai dengan perbedaan makna teks-teks agama dengan realitas historisitas. Perpaduan antara teori feminis sebagai bagian dari teori modern dan studi Islam (interpretasi kontemporer hukum agama) menawarkan solusi masalah kemanusiaan melalui keseimbangan penilaian pada wanita dan pria. Menemukan nilai-nilai Islam yang relevan dalam pengarusutamaan gender memiliki dampak positif pada keadilan sosial. Mengembangkan studi Islam sebagai cara menemukan nilai esoteris yang mendasari kehidupan dalam kerangka transformasi sosial keagamaan. Menegaskan bahwa Islam tidak hanya membahas masalah klasik dan teologis Fiqh, tetapi juga mengilhami umat manusia untuk menghakimi dan memperlakukan sesama manusia sebagai makhluk Tuhan yang bermartabat dan bermartabat sehingga wajar untuk dihormati dan diperlakukan secara adil.